2018
DOI: 10.1177/0954407018760433
|View full text |Cite
|
Sign up to set email alerts
|

A novel control approach for path tracking of a force-controlled two-wheel-steer four-wheel-drive vehicle

Abstract: This paper presents a novel approach for a force-controlled over-actuated two-wheel-steer four-wheel-drive vehicle to achieve accurate path tracking through control allocation. The control algorithm is developed by combining embedded integrator model predictive control and sequential quadratic programming–based control allocation. Based on the offset model presented in this paper, the model predictive control can generate the virtual accelerations. Using these virtual accelerations in control allocation, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In [84], vehicular ad hoc networks (VANETs) and three-valued, secure routing (VSR) are used for intelligent transport systems and vehicle control management. The study in the direct yaw control system (DYC) [85][86][87], active front steering system (AFS) [77,88], fourwheel steering system [89], collision avoidance system (CAS) [90], adaptive cruise control (ACC) [91] and acceleration slip regulation (ASR) have shown that the longitudinal drive stability and dynamic performance have been improved [92]. It is interesting to note that the different lateral acceleration and response were generated by changes in the steering wheel angle when the vehicle turns at a constant longitudinal speed.…”
Section: Advanced Technologies For Vehicle State Estimationmentioning
confidence: 99%
“…In [84], vehicular ad hoc networks (VANETs) and three-valued, secure routing (VSR) are used for intelligent transport systems and vehicle control management. The study in the direct yaw control system (DYC) [85][86][87], active front steering system (AFS) [77,88], fourwheel steering system [89], collision avoidance system (CAS) [90], adaptive cruise control (ACC) [91] and acceleration slip regulation (ASR) have shown that the longitudinal drive stability and dynamic performance have been improved [92]. It is interesting to note that the different lateral acceleration and response were generated by changes in the steering wheel angle when the vehicle turns at a constant longitudinal speed.…”
Section: Advanced Technologies For Vehicle State Estimationmentioning
confidence: 99%
“…9 Differential braking control was attached to handle path-following problems in several papers. 1012 Controllers on AFS and direct yaw-moment control (DYC) were discussed for maintaining lateral stability and reducing longitudinal velocity fluctuations. 13,14 A novel controller in a quasi-linear optimization manner was investigated in minimizing the post-impact lateral offset with respect to the desired path.…”
Section: Introductionmentioning
confidence: 99%
“…To improve ground vehicle handling stability and passenger safety, a large number of advanced vehicle-active safety dynamic control systems, such as the direct yaw control system (DYC) [1,2,3,4], anti-lock braking systems (ABS) [5,6], four-wheel steering system (4WS) [7,8], active front steering system (AFS) [2,9], active suspension system (ASS) [9,10], adaptive cruise control (ACC) [11], collision avoidance system (CAS) [12], and other advanced driver assistance systems (ADAS) towards a connected and automated driving vehicle have been developed and brought into the market in recent years [13,14,15].…”
Section: Introductionmentioning
confidence: 99%